Developing and maintaining collaborative practice: Exploring perspectives from dietetics and speech pathology about 'what works well'. Issue 1 (25th December 2018) - Croker, Anne; Brown, Leanne; Little, Alexandra; Squires, Kelly; Crowley, Elesa
Abstract : Aim: The aim was to support rich collaborative practice between two professions who frequently work together across both ordered and organic modes of collaboration. Methods: This study uses a qualitative research approach of collaborative dialogical inquiry to explore the question 'From the perspective of dietitians and speech pathologists, "what works well" for developing and maintaining collaborative practice?' We deliberately chose a context where collaborative practice is evident, University Department of Rural Health (UONDRH). Participants in the research were academics and clinicians from dietetics and speech pathology. Data were sourced from our research reflections and focus group transcriptions. Analysis was dialogical and iterative. Results: Beyond shared purpose, knowledge of roles and good communication, the notions of curiosity, willingness and momentum were at the core of 'what works well' for collaborative practice between dietitians and speech pathologists. Participant perspectives related to collaborative practice between these professions and beyond to other professions, and involved collaborative practice within and across healthcare organisations and a university setting. Conclusions: Our interpreted themes of curiosity, willingness and momentum for developing and maintaining collaborative practice highlight the importance of paying attention to the less visible and difficult to measure aspects of patient‐centred care. Questions for reflection are suggested to inform the ongoing process of developing and maintaining our and others' collaborative practice.